Influence of Density and Development Stage of Ryegrass on Glyphosate Effectiveness - FIPKE,M.V. (2019)
ABSTRACT : Glyphosate is one of the main herbicides used to control ryegrass. The objective of this research was to evaluated whether the glyphosate dose-response curve is affected by density of ryegrass plants in two phenological growth stages. To attend this objective, two experiments were carried out in greenhouse (one with Lolium multiflorum and another with Lolium rigidum) and two under field conditions. In the greenhouse experiments, the experimental design was a completely randomized design in a factorial scheme, with factor A as plant density and factor B as glyphosate doses. In the field, two experiments were carried out in a randomized block design in a split-plot scheme. Plots consisted of glyphosate doses (0, 40, 80, 120, 160, 250, and 350 g ha-1), and the subplots consisted of three ryegrass densities (8 plants m-2, 140 plants m-2 with thinning before herbicide application, and 140 plants m-2 with thinning after herbicide application). In one experiment, glyphosate was sprayed at 28 days after emergence (DAE), whereas in another the application was carried out at 51 DAE. High-density ryegrass plants required a higher herbicide dose to obtain the same level of control of low-density plants. In addition to the density effect, an increased glyphosate dose was necessary for the late application to obtain the same level of control when compared to the initial application. Herbicide effectiveness was affected by population density and plant development stage.